Practising on the poor? Healthcare workers’ beliefs about the role of medical students during their elective - Radstone, S. J. J. (Journal of medical ethics, 2005)
Medical electives have long been part of the undergraduate curriculum, and many students choose to undertake a placement in a developing country. In countries where healthcare provision is hugely underresourced, students have found themselves under pressure to exceed their role. They have been expected to diagnose and treat patients without direct supervision from a qualified doctor. Some have found themselves running clinics and wards; others have found themselves to be the most qualified person available.1,2 The British Medical Journal believes students should not take on the role of a qualified doctor, “irrespective of any encouragement which students may receive from members of the host organisations to which they are attached”.3 This includes not diagnosing, prescribing, or treating any patient without strict clinical supervision. They feel that students fail to appreciate the dangers of treatment, particularly where familiar medical problems are complicated by unfamiliar poverty. Their deontological view is saying that students should treat their work …